The ethnography of Tantra: textures and contexts of living Tantric traditions - Lorea, Carola Erika; Singh, Rohit (Sunny Press, 2023)
Presents Tantra from an ethnographic vantage point, through a series of case studies grounded in diverse settings across contemporary Asia
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Religionsausübung; Tantrismus; Südasien